Methods and compositions for inhibiting cancer cell growth - Mohamed, Suhaila; Ahmadi, Negin; Lim, Swee Ling; Mohamed Mustapha, Noordin; Rahman, Heshu Sulaiman (2014)
The present invention discloses compositions and methods for treating, as well as preventing and inhibiting blood and lung cancer by providing a safe, nutraceutical composition comprising a plant extract from the family Rubiaceae, Acanthaceae and Zingiberaceae. In more specific, the nutraceutical composition is capable of inducing apoptosis in leukemia and lung cancer cells, to reduce severity and incidence, without affecting growth of normal cells.